NAVIGATING BARRIERS: THE NEED FOR INTEGRATED HEALTH INFORMATION SYSTEM FOR TUBERCULOSIS-DIABETES CO-SCREENING - Arini, Merita; Prakoso, Denny Anggoro; Suryanto, Farid; Dewi, Arlina; Basha, Muzaitul Akma Binti Mustapa Kamal (Universitas Airlangga, 2024)
Background: Tuberculosis-diabetes mellitus (TB-DM) is a co-epidemic condition representing a double burden for high TB burden countries like Indonesia. Private primary care (PPC) in Indonesia was newly reintroduced to the TB program. Aims: This study explores the challenges PPC healthcare workers (HCWs) face in implementing TB-DM bi-directional screening and strategies to improve it. Methods: An explorative qualitative method was used by conducting two-round focus group discussions (FGDs) with HCWs (n=15) from five private clinics in Yogyakarta Special Region Province Indonesia and triangulated with 10 DM patients and the TB program manager from the provincial health office. The data were audio recorded, transcribed verbatim, and subjected to thematic analysis. Results: HCWs face complex barriers in TB-DM co-screening implementation from patients, HCWs, and health system aspects. An integrated system to remind, support decision-making, report, reduce documentation duplication, monitor, and evaluate co-screening implementation emerged as a potential strategy, although some challenges to deploy. Conclusion: Albeit HIS is promising in enhancing integrated TB-DM screening and management, a comprehensive approach and multisector roles are still needed to overcome impediments to TB-DM bidirectional screening in PPCs. Keywords: diabetes mellitus, health information system, screening, tuberculosis